O conceito de grupo: sua formação por alunos de matemática - Albuquerque, Izabel Maria Barbosa de (2005)
This work has the obective to anlyse the group concept formed by the students of the Mathematics Course at the Federal University of Campina Grande – Campina Grande Campus, as a result of their first course in abstract algebra taken in the second semester of 2002. Throughout this analysis I have tried to understand the concept of a binary operation in a set, formed by these students, the actions and operations made when dealing with problem-situations in which the group concept was explicit, and, finally, the group concept formed by them. I referred to the Lev Semenovich Vygotsky proposal about the social-historical approach when he suggested that the ones process of concept formation was essentially mediated by word, and Gérard Vergnaud’s about the theory of conceptual fields, in which ones formation of a concept was determined, particularly, by situations involving in the concept experienced by him. For this research I have applied means of investigation constituted by open questions and problem-situation facts, followed by interviews. I have noticed, in the analysis of the knowledge expressed in the writing, a high level of difficult in the making of solutions for the activities, as well as a great amount of unexpected and incoherent of the problem-solutions. The data analisis done after these interviews shows a significative decrease in the number of solutions of this nature and they reveal the criative potential of the students when they are helped by a more experienced person. These facts show the importance and need to consider, in teaching, a long process of students’involvement with problem-situation within a space permeated with a scientific debate between teacher and students and student-student, mediated by knowledge, infavoring the discussion of their solutions, doubts and creative ideas in the study of mathematical concepts, especially, the algebraic ones.